Improvement of high school biology teacher understanding on the national science competition subject through technical guidance - Anggraito, Y U; Iswari, R I; Priyono, B; Purwantoyo, E; Pukan, K K (Journal of physics. Conference series, 2021)
There has not been a single high school student in Brebes District who has successfully represented Central Java Province in the National Science Competition (NSC) in the last three years. The main problem is the teacher’s weak mastery of the subject to provide guidance to students, caused the mentoring process is not optimal. The purpose of this study was to improve the teacher mastery of subjects for teachers who were accompanying students in the NSC. This study used a one-group pretest-posttest design with a sample of 23 high school biology teachers who attended Technical Guidance (TG). The TG subjects were Ecology, Animal Physiology and Metabolism; Plant Anatomy and Physiology; and Genetics. The data obtained were pre-test and post-test scores, which were then analyzed using T-test and N-gain. The average result of the pre-test score was 40.22, and the post-test score was 70.27. There is an indication of teacher weaknesses in the application of the concept and data analysis. The results showed (1) there was a difference in the results of the participants’ post-test scores, which higher than the pre-test, (2) there was a significant increase in the scores between before and after technical guidance, (3) the N-gain was 0.51 in the moderate category. It could be concluded, Technical Guidance on NSC subjects is effective in improving the understanding of high school biology teachers in Brebes district.